Geosynthetics in tunnels and underground structures applications - Cazzuffi Daniele; Gioffrè Domenico; Luciani Andrea (E3S Web of Conferences, 2023)
Waterproofing systems of tunnels is of crucial importance for the long-term effectiveness of the underground works and for the possible impact on the surrounding environment. In conventional tunnelling, polymeric geomembranes are nowadays used with fluid barrier function, while nonwoven geotextiles and geonets are commonly employed with mechanical protection and drainage functions. After some descriptions of the main requirements of the geosynthetics used in tunnels and underground structures, the durability aspects of the materials forming the waterproofing systems are briefly outlined.